System Training Services Provided by ’Training Service Providers’ and ’In-House Trainers’-Organizational Consumers’ Perception about Service Attributes - Ganesh, S. K. G.; Bhat, M. S.; Kumar, R. B. (Indian Journal of Marketing, 2007)
Computerization has gained greater significance in various organizations in India. System products providing information solutions are being procured from system sellers or developed in-house by the Electronic Data Processing (EDP)/Information Technology (IT) department of the organizations. System users in various departments are trained by the system sellers (training service providers) or by the EDP/IT department (in-house trainers). This papers analyses the organizational consumers’ (system users’) perception about various attributes related to training services received by various organizations in Hyderabad. Factor analysis has been applied to identify the predominant factors that are to be considered by the training service providers for designing training services and delivering training to the organizational users.